The incessant inbox: Evaluating the relevance of after‐hours e‐mail characteristics for work‐related rumination and well‐being. (29th October 2020) - Minnen, Molly E.; Mitropoulos, Tanya; Rosenblatt, Alexa K.; Calderwood, Charles
Abstract: While many employees read and respond to work‐related e‐mails in the evenings after work, the mechanisms through which after‐hours e‐mailing influences well‐being remain poorly understood. In particular, there has been limited consideration of whether different characteristics of after‐hours e‐mails (frequency, duration, perceived tone) may trigger work‐related rumination that influences employee well‐being at bedtime (i.e., the end of the post‐work period). To address this gap in the literature, data were collected from 59 employees during a 5‐day daily survey period. We expected after‐hours e‐mail frequency, duration, and perceived tone to indirectly relate to employee vigour and fatigue at bedtime (two common well‐being criteria) via affective rumination and problem‐solving pondering (two major forms of work‐related rumination). Our results indicated that a more negatively perceived after‐hours e‐mail tone influenced both vigour and fatigue via affective rumination. Further, our findings suggested diverging implications of after‐hours e‐mailing frequency and duration for problem‐solving pondering, with longer duration and more frequent after‐hours e‐mailing co‐varying with higher and lower levels of this form of rumination, respectively. These findings demonstrate the importance of considering various characteristics of after‐hours e‐mailing and corresponding implications of work‐related rumination when studying employee well‐being.